The Indonesian Undergraduate Students’ Competence in Writing Introduction of Thesis Proposals: A Discourse Analysis - Setyo Karjono (Journal of English Language and Pedagogy, 2019)
Writing thesis proposal requires several competences. At the sentence level, it includes the control of word choice or diction and syntactic form. Beyond the sentence, it deals with the organization of the ideas and information into cohesive and coherent paragraphs. In practice, many students encounter difficulties in writing proposals especially the introduction section. The focus of this study was in the discourse analysis type, concerning the thesis writing which covered the organization, the unity, and coherence of paragraphs, and the syntactic form. Subjects of this research were students of a private university in Yogyakarta, Indonesia who were writing their theses as their final project. All data sources were from the undergraduate students' initial thesis writings especially the Introduction section proposed by the students from the three fields of study: English Language Teaching, Linguistics, and Literature. Findings show that: (a) Mostly the students’ proposals addressed well organization though using somewhat developed explanations, exemplifications, or details; (b)  They also displayed unity and coherence, though the connection of ideas was occasionally obscured; (c) The student’ proposals also  demonstrated inconsistent competence in syntactic structure and word choice; (d) Mostly, the student’ proposals accomplished the score level 3 for their academic writings because they did not fully meet some points of academic writing criteria. Considering the organization, unity and coherence are the most appropriate variety for the undergraduate students’ writings, the study suggests that students should be exposed to a more standard guidance or rubric of thesis writing